(untitled) (Research, Society and Development, 2022)
Changes in human behavior towards the environment, barriers to urban development, globalization and climate change are some of the factors that contribute to the occurrence and spread of infectious diseases. The incident affects three arboviruses in Brazil, Chikungunya, Dengue and Zika, which are widely disseminated by mosquito vectors distributed throughout the country, related to humans, causing major public health problems. In the absence of effective vaccines and specific treatments, it is important to maintain and integrate ongoing entomological and epidemiological surveillance to guide the country’s control and prevention approaches against these arboviroses. The Annonaceae family has been extensively studied to utilize many species as a source of insecticidal compounds with different modes of action on insects. Therefore, this work aimed to develop a natural, economical and sustainable product using Annona squamosa leaf extract as a resource against Aedes aegypti larvae. From the results, one can prove the hypothesis that the natural insecticide developed from the leaf extract of the fruit of the conde (Annona squamosa) is very effective and also effective in reducing the mortality of Aedes aegypti.